(untitled) (Research, Society and Development, 2024)
Objectives: To provide clinicians with an updated on bone grafts, biomaterial substitutes and bioactive mediators for bone regeneration techniques. Materials and Methods: A narrative review in English was conducted, prioritizing publications from the last five years. Research was carried out on databases, complemented by manual searches in relevant journals. Results: Autologous grafts showed the greatest bone gain but were associated with complications. Platelet-rich materials showed no complications, either individually or in combination. However, further research is needed on growth factors, cellular therapy, and 3D-printed scaffolds to enhance efficacy and safety in guided bone regeneration. Conclusions: The ongoing search for the optimal material is evident. Surgeon skill and flap management influence bone regeneration. Future research should focus on optimizing techniques considering individual clinical variations.